Identification and assay of steroid compounds in narrow-leaved catoptric raw material - Довгаль, Євгеній Олександрович; Гур’єва, Ірина Геннадіївна; Кисличенко, Вікторія Сергіївна; Журавель, Ірина Олександрівна (ScienceRise: Pharmaceutical Science, 2016)
Typha angustifolia L. (Narrow-leaved Catoptric) – is a widespread in Ukraine herb, that grows in damp places, especially along rivers, marshy places, etc. Herbal material of Narrow-leaved Catoptric is used in medicine for treatment of many diseases. Inflammation is one of the indications for Narrow-leaved Catoptric use. As it is known, steroid compounds have a prominent anti-inflamatory activity, complex research of this group of compounds, as well as qualitative and quantitative determination of steroid compounds in leaves, fruit, rhizomes and roots of Narrow-leaved Catoptric became relevant. The aim of the given research was qualitative and quantitative determination of steroid compounds in leaves, fruit, rhizomes and roots of Typha angustifolia L. Methods. Wet chemistry reactions were used for identification of steroid compounds. Quantitative determination of steroid compounds in herbal material of Narrow-leaved Catoptric was carried out using spectroscopy method. Results. In result of research, steroid compounds were determined in leaves, fruit, rhizomes and roots of Typha angustifolia L. While analyzing the obtained data about the sum of steroid compounds content, it was determined, that the highest content of this group of compounds was in Typha angustifolia L. leaves, slightly less – in rhizomes, and trace amount – in fruit. Conclusion. Results of the given study can be used for determination and obtaining of substances and original phytotherapeutic remedies on the basis of the given herbal material, as well as for determination of standardization parameters of Typha angustifolia L.